Crime in Tourism: A Systematic Literature Review and Bibliometric Analysis - Eylem Baş; Engin Bayraktaroğlu (Ceza Hukuku ve Kriminoloji Dergisi)
Tourism is closely related to social factors. This situation also leads to a relationship between tourism and crime. The increase in tourist movements increases the population of destinations, and the increasing population creates a suitable environment for criminal activities. Social, economic, cultural differences, environmental conditions, and inadequate security measures affect the crime activities observed within tourism. From this perspective, crime in tourism is a multi-dimensional problem that needs to be addressed in detail. It is also essential to evaluate crime patterns within the tourism phenomenon. This study evaluated 273 articles indexed in the Web of Science Core Collection by a systematic literature review and bibliometric analysis. The articles were subjected to structured content analysis, and a literature review was conducted within the scope of the study. Various variables such as author, citation, and publication were examined using bibliometric techniques such as co-occurrence, network, and co-citation analysis. According to the results, it was seen that multi-dimensional collaborations should be carried out to solve the problems arising within the scope of crime in tourism. Among these, international, interdisciplinary, and inter-institutional collaborations are at the forefront. In addition, long-term studies should be conducted to collect real-time data, and preventive measures and policies should be developed. Interdisciplinary studies should be encouraged to create a safer environment for tourists and hosts in destinations.